KONSTRUKSI REALITAS CITRA HAJI DALAM SINETRON TUKANG BUBUR NAIK HAJI - Yuyu Aprila; Suyanto " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
Hajj image played by H.Muhidin in Tukang Bubur Naik Haji the Soap Opera very interesting to study because hajj is in this soap opera is very different from the actual hajj according to Islamic law could become a role model in society. But in this soap opera H.Muhidin have not good behavior are strictly forbidden Allah as arrogant, envy and so forth. The purpose of this research is to find out the reality construction of hajj image in Tukang Bubur Naik Haji the soap opera episode 276 by separating denotation, connotation and myth.This research used qualitative methods descriptive which the data was obtained through interviews, documentation, and reference materials. As well as using semiotic analysis technique developed by Roland Barthes and the theory o fself-image to to know the reality construction of hajj image in Tukang Bubur Naik Haji the soap opera episode 276. This research presented the subject is the text of Tukang Bubur Naik Haji the soap opera. While the research object is the scene-scene in Tukang Bubur Naik Haji the soap opera episode 276 itself.The results showed that the reality construction in Tukang Bubur Naik Haji the soap opera episode 276 is negative and a positive hajj image. The reality construction of the negative hajj image or pilgrimage is not commendable, played by H.Muhidin constructed in Tukang Bubur Naik Haji episode 276 the soap opera among others, arrogant, angry, envy and prejudice. While reality construction of the positive hajj image or pilgrimage is commendable, played by H.Sulam constructed in Tukang Bubur Naik Haji episode 276 the soap opera among others, include praise, friendly and patient.Keywords : Tukang Bubur Naik Haji the soap opera, the reality construction, semiotics of Roland Barthes.